Microstructural alterations in white matter and related neurobiology based on the new clinical subtypes of Parkinson's disease - Yuan, Xiaorong; Yu, Qiaowen; Liu, Yanyan; Chen, Jinge; Gao, Jie; Liu, Yujia; Song, Ruxi; Zhang, Yingzhi; Hou, Zhongyu (Frontiers in Neuroscience, 2024)
The advent of new clinical subtyping systems for Parkinson's disease (PD) has led to the classification of patients into distinct groups: "mild motor predominant (PD-MMP)", "intermediate (PD-IM)", and "diffuse malignant (PD-DM)". Our goal was to evaluate the efficacy of diffusion tensor imaging (DTI) in the early diagnosis, assessment of clinical progression, and prediction of prognosis across these PD subtypes. Additionally, we sought to delve into the pathological mechanisms behind white matter damage through the use of SPECT and CSF analyses.We classified 135 de novo PD patients based on new clinical criteria and followed them up after 1 year, along with 45 HCs. We utilized tract-based spatial statistics to assess microstructural white matter changes at baseline, and employed multiple linear regression to examine the associations between DTI metrics and clinical data at baseline and after follow-up.Compared to HCs, patients with the PD-DM subtype demonstrated reduced fractional anisotropy (FA), increased axial diffusivity (AD), and elevated radial diffusivity (RD) at baseline. The FA and RD values correlated with the severity of motor symptoms, with RD also linking to cognitive performance. Changes in FA over time was found to be in sync with changes in motor scores and global composite outcome measures. Furthermore, baseline AD values and their rate of change were related to alterations in semantic verbal fluency. We also discovered the relationship between FA values and the levels of α-synuclein and β-amyloid. Reduced dopamine transporter uptake in the left putamen correlated with RD values in superficial white matter, motor symptoms, and autonomic dysfunction at baseline, as well as cognitive impairments after 1 year.The PD-DM subtype is characterized by more severe clinical symptoms and a faster progression when compared to the other subtypes. DTI, a well-established technique, facilitates the early identification of white matter damage, elucidates the pathophysiological mechanisms of disease progression, and predicts cognitively related outcomes.SPECT and CSF analysis results provide further explanations for the specific pattern of white matter damage in patients with the PD-DM subtype.